Long-range and short-range dihadron angular correlations in central PbPb collisions at psNN = 2:76 TeV - Chatrchyan, S. (2011)
First measurements of dihadron correlations for charged particles are presented for central PbPb collisions at a nucleon-nucleon center-of-mass energy of 2.76TeV over a broad range in relative pseudorapidity (Δν) and the full range of relative azimuthal angle (Δø). The data were collected with the CMS detector, at the LHC. A broadening of the away-side (Δø y≈ π) azimuthal correlation is observed at all Δν, as compared to the measurements in pp collisions. Furthermore, long-range dihadron correlations in Δν are observed for particles with similar ø values. This phenomenon, also known as the \ridge, persists up to at least jΔνj = 4. For particles with transverse momenta (pT) of 2-4 GeV/c, the ridge is found to be most prominent when these particles are correlated with particles of pT = 2-6 GeV/c, and to be much reduced when paired with particles of pT = 10-12 GeV/c. Copyright CERN.